Comments on Neoconocephalus Karny, 1907 (Orthoptera, Tettigoniidae, Conocephalinae) species described by Salvador de Toledo Piza Jr.: The first contribution to the knowledge of South American species - Antunes, André Fonseca; Souzadias, Pedro G. B.; Takiya, Daniela Maeda (Zootaxa, 2025)
Neoconocephalus Karny, 1907 is the third largest genus of Tettigoniidae with 129 valid species. Distributed throughout the American continents, it has been the subject of several faunal, bioacoustic, and phylogenetic studies, but never focused on the South American fauna. Type material of 19 Neoconocephalus species described by Professor Salvador de Toledo Piza Júnior (1898–1988) deposited at the Museu de Entomologia of the Escola Superior de Agricultura “Luiz de Queiroz” (MELQ), Universidade de São Paulo, Brazil, was revised. The following nine species are considered valid (with proposed junior synonyms): Neoconocephalus boraceae Piza, 1952, N. boraceanus Piza, 1983, N. corumbaensis Piza, 1969, N. curitibensis Piza, 1952 (= N. rioclarensis Piza, 1975 syn. nov.), N. gaucho Piza, 1969 (= N. creusae Piza, 1970 syn. nov.), N. guyvalerioi Piza, 1972 (= N. precarius Piza, 1975 syn. nov., = N. matogrossensis (Piza, 1983) syn. nov.), N. incertus (Piza, 1958) (= N. ferreirai (Piza, 1971) syn. nov., = N. lavrensis Piza, 1971 syn. nov., = N. paravicinus Piza, 1973 syn. nov., = N. riparius (Piza, 1983) syn. nov., = N. xiphophorus Piza, 1975 syn. nov.), N. karollenkoi Piza, 1983, and N. vittatus (Piza, 1973) (= N. spitzi Piza, 1983 syn. nov.). Based on the study of additional specimens deposited in five other Brazilian collections, these valid species are redescribed and external morphology photographs are provided. In addition, known distribution of these species is updated, including 23 new records for the nine species for ten Brazilian states.